STUDY OF ANTIOBESITY ACTIVITY OF POLYHERBAL FORMULATION IN CORRELATION WITH ANTIDIABETIC ACTIVITY - Deepak, Jain; Anurekha, Jain (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to develop a polyherbal formulation using four different herbs using obese diabetic rat’s model. Methods: Rats received high-fat diet and alloxan was injected intraperitoneal to rats for induction of diabetes. In the preventive experiment, diabetic rats received Momordica charantia Linn. (200 and 400 mg/kg/day p.o), Eugenia jambolana Linn. (200 and 400 mg/kg/day p.o), Ziziphus mauritiana (200 and 400 mg/kg/day p.o), Acacia catechu (AC) (200 and 400 mg/kg/day p.o), and aqueous extract of all extracts (100 and 200 mg/kg/day p.o). Diabetic rats were also treated with glibenclamide (5 mg/kg p.o.) and orlistat (60 mg/kg/day p.o.) as reference standards. Results: The results showed that the extract of M. charantia Linn., E. jambolana Linn., Z. mauritiana, and AC significantly (p<0.05) inhibited body weight gain, blood glucose, triglyceride, total cholesterol, low-density lipoprotein (LDL), very LDL, high-density lipoprotein cholesterol, serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, and fasting blood glucose in a dose-dependent manner. Extracts treated rats at doses of 200 and 400 mg/kg improved dyslipidemia in high-fat diet (HFD)-induced obese rats by enhancing their lipid metabolism when compared to the HFD control. Conclusion: The results obtained in this research work clearly showed that taken together the extract of M. charantia Linn., E. jambolana Linn., Z. mauritiana Lam. AC Willd., and aqueous extract of all extracts has potential as a preventive agent for type 2 diabetes mellitus (and possibly obesity) and deserves clinical trial in the near future.